Self-scheduling of joint wind power and NaS battery plants in spinning reserve and energy markets - Tahmasebi M.; Pasupuleti J. (Engineering and Scientific Research Groups, 2023)
Distributed Energy Resources (DER) are small-scale power generation and storage technologies located close to the customer side. One of the DER is wind power generation which is a valuable supplement for the conventional energy sources. The integration of intermittent wind generation in power system requires the inclusion of more inventive and sophisticated methods for the planning of power system operation. At a high penetration level, additional reserve capacity intervention is necessary to cover the shortage in generation when a sudden variation of wind occurs. One of the strategies that can be offered to solve this problem is the use of electrical energy storage. A new technology of electric energy storage is Natrium sulfur (NaS) battery system. Lately, this technology is intensely considered because of its sufficient technological maturity and less environmental impact. This work focuses on the economic operation of generation company (Genco) consisting of wind power plant (WPP) and NaS battery plant (NaSP) in a competitive electricity market and the WPP intermittent coverage. The researcher in this paper uses Self-Scheduling (SS) method to derive maximum expected profit from the Energy and Spinning Reserve Markets. The self-scheduling problem of the Genco is formulated and solved as a mixed integer nonlinear programming (MINLP) problem. The numerical results for a case study are presented in this paper. © JES 2014.